EVEKTIVITAS PELAKSANAAN RENCANA TATA RUANG WILAYAH KOTA SALATIGA DALAM IJIN PERUBAHAN PENGGUNAAN TANAH - SURYANDARI, NURAKHMI (Dinamika Hukum, 2015)
The purpose of this study was to determine the implementation of changes in land use from agriculture to non-agriculture in Salatiga. Background research that in order to establish guidelines, and as an operational tool for the direction of development in Salatiga by exploiting the spatial effective, efficient, effective, harmonious, balanced and sustainable in order to improve social welfare and defense and security, has been established Regional Regulation No. 4 year 2011 on Spatial Planning Salatiga years 2010-2030. In this study used empirical juridical approach, with analytic descriptive research specifications describe laws applicable undangn associated with legal theory and practice of positive law concerning the problems studied. This study uses qualitative and quantitative data analysis, with an emphasis on qualitative approach in accordance with the goals and objectives of the study are to be achieved. The results showed that the implementation of the change of use of agricultural land to non-agricultural conducted on the basis of Technical Considerations Land issued by the Land Office of Salatiga, then by the Committee Consideration of Change Land Use Salatiga, conducted a meeting / session discussed the request to change the land use proposed and carried out a review field. The results of the hearing set forth in the Minutes. Licensing changes outlined in the Land Use Decree signed by the Head Office of Salatiga. Keywords: Implementation of changes in the use of agricultural land to non-agricultural in Salatiga